Thalidomide, clarithromycin, lenalidomide and dexamethasone therapy in newly diagnosed, symptomatic multiple myeloma. Issue 12 (December 2014) - Mark, Tomer M.; Bowman, Isaac A.; Rossi, Adriana C.; Shah, Manan; Rodriguez, Melissa; Quinn, Ryann; Pearse, Roger N.; Zafar, Faiza; Pekle, Karen; Jayabalan, David; Ely, Scott; Coleman, Morton; et al.
Abstract We studied T-BiRD (thalidomide [Thalomid®], clarithromycin [Biaxin®], lenalidomide [Revlimid®] and dexamethasone) in symptomatic, newly diagnosed multiple myeloma. In 28-day cycles, patients received dexamethasone 40 mg/day on days 1, 8, 15, 22, clarithromycin 500 mg twice daily on days 1–28; lenalidomide 25 mg/day on days 1–21; and thalidomide 100 mg/day (50 mg/day on days 1–7 of cycle 1 only) on days 1–28. Twenty-six patients received a median of 6 cycles (range 0–41). Overall response rate (ORR) was 80% for the group and 100% in 11 patients who underwent autologous stem cell transplantation as part of first-line therapy. The 4-year overall survival rate was 74.9%, and the median progression-free survival was 35.6 months. Eight patients discontinued due to regimen toxicity. Grade 3 non hematologic toxicity affected 12 patients (46.2%). T-BiRD is a highly active regimen with potential toxicity limitations. ClinicalTrials.gov identifier: NCT00538733